The Role Of Metacognitive Strategies In The Creation Of Discourse - Mohammed, NAOUA (University of El-oued, 2018)
Bachman and Palmer (1996) define communicative competence as the ability to create and interpret discourse. According to the authors, this ability is organized into two main constituents: language competence and metacognitive strategies. The former refers to the domain of information stored in memory; and encompassing grammatical, textual, functional, and sociolinguistic knowledge. The latter refer to the metacognitive, the neurological and physiological processes that provide a cognitive management for language use. On the one hand, these mental processes make it possible for the different sectors of language knowledge to interact internally to create language. On the other hand, they serve as a mediator between these internal traits and the external context. This paper attempts to shed light on the role of metacognition in the creation and interpretation of discourse. يعرف بكمان وبالمار )6991 )الكفاءة التواصلية بأنها المقدرة على إنشاء وفهم الخطاب. وتتشكل هذه الكفاءة من مكنونين أساسيين هما الكفاءة اللغوية واالستراتيجيات العرفانية. تتضمن األولى المعلومات اللغوية المخزنة في الذاكرة في المجاالت النحوية, النصية, الوظيفية واالجتماعية. وتعرف األخيرة)الكفاءة االستراتيجية( بأنها تلك العمليات اإلردراكية, العصبية والسيكولوجية التي توفر التحكم العرفاني الستعماالت اللغة. تقوم الكفاءة االستراتيجية بتنشيط التفاعل بين مكونات المعرفة اللغوية لتشكيل الخطاب, كما تقوم بالربط بين هذه الخاصيات الذهنية والسياق الخارجي. تحاول هذه الورقة تسليط األضواء على ردور استراتيجيات ما وراء اإلردراك في إنشاء وفهم الخطاب.
Article .Ex Professor. Vol 03. N 01 Université d'El-Oued
Keywords: communicative competence - discourse - mental processes - metacognitive strategies; الكفاءة التواصلية الخطاب العمليات الذهنية استراتيجيات ما وراء االدراك.